If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4y + 26)(3x + -5) = 0 Reorder the terms: (26 + 4y)(3x + -5) = 0 Reorder the terms: (26 + 4y)(-5 + 3x) = 0 Multiply (26 + 4y) * (-5 + 3x) (26(-5 + 3x) + 4y * (-5 + 3x)) = 0 ((-5 * 26 + 3x * 26) + 4y * (-5 + 3x)) = 0 ((-130 + 78x) + 4y * (-5 + 3x)) = 0 (-130 + 78x + (-5 * 4y + 3x * 4y)) = 0 Reorder the terms: (-130 + 78x + (12xy + -20y)) = 0 (-130 + 78x + (12xy + -20y)) = 0 (-130 + 78x + 12xy + -20y) = 0 Solving -130 + 78x + 12xy + -20y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '130' to each side of the equation. -130 + 78x + 12xy + 130 + -20y = 0 + 130 Reorder the terms: -130 + 130 + 78x + 12xy + -20y = 0 + 130 Combine like terms: -130 + 130 = 0 0 + 78x + 12xy + -20y = 0 + 130 78x + 12xy + -20y = 0 + 130 Combine like terms: 0 + 130 = 130 78x + 12xy + -20y = 130 Add '20y' to each side of the equation. 78x + 12xy + -20y + 20y = 130 + 20y Combine like terms: -20y + 20y = 0 78x + 12xy + 0 = 130 + 20y 78x + 12xy = 130 + 20y Reorder the terms: -130 + 78x + 12xy + -20y = 130 + 20y + -130 + -20y Reorder the terms: -130 + 78x + 12xy + -20y = 130 + -130 + 20y + -20y Combine like terms: 130 + -130 = 0 -130 + 78x + 12xy + -20y = 0 + 20y + -20y -130 + 78x + 12xy + -20y = 20y + -20y Combine like terms: 20y + -20y = 0 -130 + 78x + 12xy + -20y = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-65 + 39x + 6xy + -10y) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-65 + 39x + 6xy + -10y)' equal to zero and attempt to solve: Simplifying -65 + 39x + 6xy + -10y = 0 Solving -65 + 39x + 6xy + -10y = 0 Move all terms containing x to the left, all other terms to the right. Add '65' to each side of the equation. -65 + 39x + 6xy + 65 + -10y = 0 + 65 Reorder the terms: -65 + 65 + 39x + 6xy + -10y = 0 + 65 Combine like terms: -65 + 65 = 0 0 + 39x + 6xy + -10y = 0 + 65 39x + 6xy + -10y = 0 + 65 Combine like terms: 0 + 65 = 65 39x + 6xy + -10y = 65 Add '10y' to each side of the equation. 39x + 6xy + -10y + 10y = 65 + 10y Combine like terms: -10y + 10y = 0 39x + 6xy + 0 = 65 + 10y 39x + 6xy = 65 + 10y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 7-15=3x+1 | | 9x+25=2x+6 | | 3+2(3n+2)=-41 | | .5x+3=.75x-7.75 | | 12(x)+9=300 | | 41k+11=16 | | 5=7+2x | | 12x+(7-x)2= | | x/3=2/9 | | 2(x+10)=4(x-2) | | -8(4+9x)=3(x-1) | | 25t+30b=750 | | 3x+1=1-3x | | -60+40x=20x | | (t)+2.7=4.5 | | -7(y-2)=-2y+39 | | 6(k-7)-(8+9k)=-4k | | 8n-3(5)= | | x^2+4x=5x | | -2x+21=7x-15 | | 8(2x-4)+5(3x+6)=29 | | (2x+28)(4x+10)= | | -3x+1=-2(3x+10) | | 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 | | -3(e+4)=4w-5 | | -3+2x=-x-6 | | 1-6x=5-4x | | 22-44= | | 13x+9=-15 |